Action of a Proteolytic Enzyme Inhibitor on Blood Coagulation in Vitro - Blombäck, B; Blombäck, Margareta; Olsson, P (Thrombosis and Haemostasis, 1967)
The action of the kallikrein and trypsin inhibitor, Trasylol, has been studied in a three-stage thrombin generation system. It has been found that Trasylol inhibits one or several of the early reactions of blood coagulation. The inhibition of the early stages is dependent on the concentration of inhibitor, serum factors and factor VIII. The activation of factor V by tiger snake venom is not inhibited by Trasylol. The inhibition is most probably on one or several of the reactions preceding the factor V involved step.Some other known antifibrinolytic agents have also been tested for anti-coagulation activity.